ANALISIS KEBUTUHAN PETUGAS KODER KLAIM JKN MENURUT ABK KES DI RUMAH SAKIT JIWA GRHASIA - Vidya Widowati; Elsye Maria Rosa (Universitas Duta Bangsa Surakarta, 2023)
Adequate and competent Health Human Resources are needed to manage the Jaminan Kesehatan Nasional (JKN) program on an ongoing basis. Calculation of needs can use Analisis Beban Kerja Kesehatan (ABK Kes) according to PMK No 33 of 2015. According to information obtained from interviews with a claim officer, there is 1 Medical Recorder and Health Information (PMIK) who served as a coder to code for JKN claims. This resulted in the reimbursement of service costs from third parties to the hospital being late. The aim of the study was to calculate the need for coder officers using the ABK Kes method for JKN claim. This research method is qualitative with a case study approach. The results of the study showed that the number of coder officers needed with the Kes ABK method was 2 people, so it was necessary to meet the required staff.